PENGARUH BERBAGAI TAKARAN PUPUK KANDANG DOMBA TERHADAP PERTUMBUHAN TANAMAN PEGAGAN (Centela asiatica L) - Lia Sugiarti (Paspalum: Jurnal Ilmiah Pertanian, 2016)
The purpose of this study was to determine the effect of various doses of sheep manure on crop growth gotu kola (Centela asiatica L). This experiment was conducted in October 2014 - February 2015 at the Experimental Faculty of Agriculture, University Winaya Mukti Andisol to soil type. The experimental design used is a randomized block design  simple pattern, consisting of six sheep manure treatment dose was repeated four times. The treatment dose of sheep manure consists of: A = without fertilizer; B = 5 t ha-1; C = 10 ton ha-1; D = 15 ton ha-1; E = 20 ton ha-1; F = 25 t ha-1. Results show 1) Provision of sheep manure pegagan effect on plant growth. 2) The dose of sheep manure 20-25 ton ha-1 affects the kindest to the number of leaves, number of tillers, and the number of tendrils primer at 8 MST and 12 weeks after planting, and root dry weight and dry weight pupus plant gotu kola at 12 MST .